Collecting biological material from palliative care patients in the last weeks of life: a feasibility study. Issue 11 (10th November 2016) - Coyle, Séamus; Scott, Aileen; Nwosu, Amara Callistus; Latten, Richard; Wilson, James; Mayland, Catriona R; Mason, Stephen; Probert, Chris; Ellershaw, John
Abstract : Objective: To assess the feasibility of prospectively collecting biological samples (urine) from palliative care patients in the last weeks of life. Setting: A 30-bedded specialist hospice in the North West of England. Participants: Participants were adults with a diagnosis of advanced disease and able to provide written informed consent. Method: Potential participants were identified by a senior clinician over a 12-week period in 2014. They were then approached by a researcher and invited to participate according to a developed recruitment protocol. Outcomes: Feasibility targets included a recruitment rate of 50%, with successful collection of samples from 80% who consented. Results: A total of 58 patients were approached and 33 consented (57% recruitment rate). Twenty-five patients (43%) were unable to participate or declined; 10 (17%) became unwell, too fatigued, lost capacity, died or were discharged home; and 15 (26%) refused, usually these patients had distressing pain, low mood or profound fatigue. From the 33 recruited, 20 participants provided 128 separate urine samples, 12 participants did not meet the inclusion criteria at the time of consent and 1 participant was unable to provide a sample. The criterion for a urinary catheter was removed for the latter 6 weeks. The collection rate during the first 6 weeks was 29% and 93% for the latter 6 weeks. Seven people died while the study was ongoing, and another 4 participants died in the following 4 weeks. Conclusions: It is possible to recruit and collect multiple biological samples over time from palliative care patients in the last weeks and days of life even if they have lost capacity. Research into the biological changes at the end of life could develop a greater understanding of the biology of the dying process. This may lead to improved prognostication and care of patients towards the end of life.